If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 4 + 3 + 6 = 7x + 3 + 6x Reorder the terms: 4 + 3 + 6 + 10x = 7x + 3 + 6x Combine like terms: 4 + 3 = 7 7 + 6 + 10x = 7x + 3 + 6x Combine like terms: 7 + 6 = 13 13 + 10x = 7x + 3 + 6x Reorder the terms: 13 + 10x = 3 + 7x + 6x Combine like terms: 7x + 6x = 13x 13 + 10x = 3 + 13x Solving 13 + 10x = 3 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 13 + 10x + -13x = 3 + 13x + -13x Combine like terms: 10x + -13x = -3x 13 + -3x = 3 + 13x + -13x Combine like terms: 13x + -13x = 0 13 + -3x = 3 + 0 13 + -3x = 3 Add '-13' to each side of the equation. 13 + -13 + -3x = 3 + -13 Combine like terms: 13 + -13 = 0 0 + -3x = 3 + -13 -3x = 3 + -13 Combine like terms: 3 + -13 = -10 -3x = -10 Divide each side by '-3'. x = 3.333333333 Simplifying x = 3.333333333
| 7(x+9)=4[x-(6-x)] | | 3(x-3)+16=2(x+5) | | 6x+6= | | 10x+2+4x+7=13x+3 | | 12y-9=16y+19 | | 9x-3=3+8x | | 7x+3y=16 | | 23-6x=-61 | | v(4v-24)=-6 | | -8y+5=-9y+3 | | h^2+26h-10=0 | | -6y+4=7y+5 | | 27x+13x=73 | | 3x^2-3x+5=0 | | 5p+5=7-4p | | x-2x+5=5 | | X^2+11x+13=0 | | (3x+7)(x+1)=10 | | 9-41= | | x^2-30x+125=0 | | 2x(x+8)+15=0 | | g^2-8g+11=0 | | 2x-5y=1 | | 5(x+6)=8+5x | | 3x^2+2x+8=0 | | d^2+22d+121=18 | | 8x+3y=8 | | 9x^10=4x^9+41 | | b^2-8b+17=7 | | 15x^2=3x+7 | | 4p+3=10+3p | | 4p+3=10+3 |